2019
DOI: 10.1016/j.copsyc.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial attention alters visual appearance

Abstract: Does attention alter appearance? This critical issue, debated for over a century, remains unsettled. From psychophysical evidence that covert attention affects early vision-it enhances contrast sensitivity and spatial resolution-and from neurophysiological evidence that attention increases the neuronal contrast sensitivity (contrast gain), one could infer that attention changes stimulus appearance. Surprisingly, few studies have directly investigated this issue. Here we developed a psychophysical method to dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 89 publications
6
80
0
Order By: Relevance
“…More recently, cognitive psychological studies have characterized the particular ways, in which attention can influence perception, from low-level visual features to high-level perceptual judgments (for review see ref. 43 ). For example, a large body of research has demonstrated that both automatic attention and voluntary attention to particular visual stimuli increases perception of both contrast and color saturation 44,45 .…”
Section: Attention and Cognitionmentioning
confidence: 99%
“…More recently, cognitive psychological studies have characterized the particular ways, in which attention can influence perception, from low-level visual features to high-level perceptual judgments (for review see ref. 43 ). For example, a large body of research has demonstrated that both automatic attention and voluntary attention to particular visual stimuli increases perception of both contrast and color saturation 44,45 .…”
Section: Attention and Cognitionmentioning
confidence: 99%
“…If the main model reflects the enhanced response state of an attended region, we can implement the withdrawal of attention by reducing Rmax. Reducing this parameter would mirror the kinds of reductions seen in neural contrast response functions (Buracas & Boynton, 2007;Gandhi et al, 1999;Luck et al, 1997), and would also reduce contrast sensitivity and perceived contrast judgments (assuming that perceived contrast is strongly linked to contrast response magnitude) in similar ways to what is observed psychophysically (Carrasco et al, 2000(Carrasco et al, , 2004Carrasco & Barbot, 2019;John M. Foley & Schwarz, 1998;Huang & Dobkins, 2005).…”
Section: Attentionmentioning
confidence: 87%
“…Journal of Vision, 19(12):17, 1-13, https://doi.org/10.1167/19.12.17. Braun, 1999), and alters appearance (Carrasco & Barbot, 2019).…”
Section: Introductionmentioning
confidence: 99%